Relation of higher-frequency oscillatory activity to white matter changes and to core mechanisms of attention. Issue 2 (3rd April 2017) - Hopfinger, Joseph B.
ABSTRACT: Voelker et al. discuss the potentially critical role of white matter changes underlying the effects of training. In regard to the specific types of neural activities and processes related to these changes, the authors focus on theta rhythms and the speed of manual response times. However, white matter changes likely affect brain oscillatory activity at multiple frequencies, and recent findings suggest structural connections may be even more important for higher frequency functional connectivity. Furthermore, activity in the gamma frequency range has been implicated in basic mechanisms of attention, and changes in these core processes could underlie improvements across multiple tasks.